SOSIALISASI ADOPSI TEKNOLOGI INFORMASI OLEH USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KECAMATAN MEDAN DELI - Ramli Ramli; Dody Hidayat (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2020)
This community service activity is carried out in the Medan Labuhan sub-district of North Sumatra with 41 participants, namely mothers of micro, small and medium enterprises (MSMEs) and community members who have a business spirit (entrepreneurship) and are opening their business in that location. One of the problems faced by MSMEs is the problem of marketing their business products. For this reason, socialization is needed that can provide knowledge related to existing problems. In connection with the publication of the Universitas Harapan Medan community service team, socializing how MSME players in Medan Labunan District can adopt Information Technology to increase the competitiveness of the results of their businesses. For example, product packaging can use graphic design technology. Marketing can be done using social media (SMS, WA, Facebook, Instagram), blogs, and the web. This community service is carried out by the socialization method, namely lectures, demonstrations and questions and answers, the material is packaged in a powerpoint and displayed using an infocus. The results of the activities that have been carried out have very high interest from the participants, this can be seen from the participants' awareness and activity in asking questions during the question and answer session.